PENGARUH TINGKAT PENGETAHUAN DAN PENDAPATAN KELUARGA TERHADAP KURANG ENERGI KRONIK (KEK) PADA IBU HAMIL - Fitriatul Masdiah; Eneng Emi Saputri; Febi Ratnasari (Nusantara Hasana Berdikari, 2021)
The proportion of the risk of KEK to the WHO expectant mother of 15-47%, Indonesia aged 15-19 years by 33.5%, 20-24 years of 23.3%, pregnant women aged 25-29 years for 16.7%, pregnant women after 30-34 years of 12.3%, pregnant women aged 35-39 years for 8.5%, pregnant women aged 40-44 years at 6.5%, at the age of 45-49 occurred an increase of 11.1 To analyse the level of knowledge and family income to less chronic energy KEK in pregnant women. Review this literature using the literature method of review. Out of 10 journals acquired some level of family income knowledge to KEK in pregnant women.